Creative content production strategies for religious outreach materials on social media - Khusairi, Abdullah (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2025)
Purpose – This study formulates a strategic framework for religious counselors in producing creative and effective da’wah content on social media. It responds to the urgent need for transitioning from conventional sermon-based communication to multiplatform strategies that align with digital audience behavior and algorithmic engagement. Method – An exploratory, qualitative design was employed, utilizing van Dijk's Critical Discourse Analysis (CDA). The dataset comprises 50 short videos purposively collected from TikTok, YouTube Shorts, and Instagram Reels (January–June 2025), selected based on their thematic relevance and audience engagement (more than 10,000 views or 100 likes). Each video was examined at macro (theme), mezzo (narrative), and micro (language) levels to identify meaning construction and ideological framing. Result – The findings reveal that audience engagement in digital da'wah is primarily driven by brevity, emotional proximity, and contextual themes rather than clerical authority. Religious messages that employ informal storytelling, humor, and local language tend to achieve a stronger connection with the audience. These dynamics reflect a transformation of religious authority from institutional to participatory and algorithmic forms. Implication – The study provides a practical model for religious counselors to enhance digital literacy, narrative creativity, and ethical awareness in content production. It encourages the institutionalization of digital training within religious outreach programs under the Ministry of Religious Affairs. Originality/Value – This research fills a conceptual gap in the existing literature by integrating critical discourse analysis with creative media production. It contributes to the emerging scholarship on digital religion through a model that bridges theological communication, media literacy, and participatory culture. *** Tujuan – Studi ini merumuskan kerangka kerja strategis bagi konselor agama dalam menghasilkan konten da’wah yang kreatif dan efektif di media sosial. Studi ini menanggapi kebutuhan mendesak untuk beralih dari komunikasi berbasis khotbah konvensional ke strategi multiplatform yang selaras dengan perilaku audiens digital dan keterlibatan algoritmik. Metode – Desain eksploratif kualitatif digunakan, dengan memanfaatkan Analisis Diskursus Kritis (CDA) van Dijk. Data set terdiri dari 50 video pendek yang dikumpulkan secara purposif dari TikTok, YouTube Shorts, dan Instagram Reels (Januari–Juni 2025), dipilih berdasarkan relevansi tematik dan keterlibatan audiens (lebih dari 10.000 tayangan atau 100 suka). Setiap video dianalisis pada tingkat makro (tema), mezzo (narasi), dan mikro (bahasa) untuk mengidentifikasi konstruksi makna dan bingkai ideologis. Hasil – Temuan menunjukkan bahwa keterlibatan audiens dalam da'wah digital terutama dipengaruhi oleh kesederhanaan, kedekatan emosional, dan tema kontekstual, bukan otoritas keagamaan. Pesan keagamaan yang menggunakan cerita informal, humor, dan bahasa lokal cenderung membangun koneksi yang lebih kuat dengan audiens. Dinamika ini mencerminkan transformasi otoritas keagamaan dari bentuk institusional menjadi partisipatif dan algoritmik. Implikasi – Studi ini menyediakan model praktis bagi konselor agama untuk meningkatkan literasi digital, kreativitas naratif, dan kesadaran etis dalam produksi konten. Hal ini mendorong institusionalisasi pelatihan digital dalam program penyebaran agama di bawah Kementerian Agama. Orisinalitas/Nilai – Penelitian ini mengisi celah konseptual dalam literatur yang ada dengan mengintegrasikan analisis wacana kritis dengan produksi media kreatif. Hal ini berkontribusi pada perkembangan kajian tentang agama digital melalui model yang menghubungkan komunikasi teologis, literasi media, dan budaya partisipatif.